Utilization of CAAT in Continuous Auditing: A Case Applied to the Ministry of Health, Peru 2022-2023 - Gloria Robel, Edgar; Ascencio Yuncaccallo, Angie; Vicente Mamani, Mayra; Chávez Díaz, Jorge; Larios Soldevilla, Omar Alexis; Flores Peraltilla, Aisha; Martínez López, Renato Oswaldo (LACCEI, 2024)
Abstract - This article presents an analysis of the application of the IDEA technological tool, developed by CaseWare, as a technique to streamline audit processes in the detection of irregularities in government spending, to guarantee the adequate allocation of public resources. The focus is on data review and detection of fraud, suspicious operations, errors, among others. The implementation of the audit using Computer Assisted Audit Techniques (TAACs) is highlighted and its application is illustrated in the context of the advertising expenses of the Ministry of Health (MINSA). A specific case related to suppliers and number of contracts for advertising expenses is explored, where the use of these techniques facilitates the detection of unusual variations and possible errors in the management of funds allocated to advertising for the 2022 and 2023 campaign. of the MINSA. The application of Auditing demonstrates its effectiveness by continuously testing controls, reporting the results immediately after the occurrence of an event or shortly after. This software's ability to perform comprehensive and precise analysis of large data sets allows patterns and discrepancies to be identified, thus offering a clearer and more detailed view of financial flows.Keywords - Continuous auditing, CAAT, fraud detection, public expenditures